Acetylsalicylic acid supplementation improves protein utilization efficiency while vitamin E supplementation reduces markers of the inflammatory response in weaned pigs challenged with enterotoxigenic E. coli. Issue 1 (December 2016) - Kim, Jae; Mullan, Bruce; Black, John; Hewitt, Robert; van Barneveld, Robert; Pluske, John
Abstract Background This experiment was conducted to test the hypothesis that vitamin E (Vit E) and acetylsalicylic acid (ASA), a cyclooxygenase-2 (COX-2) inhibitor, will additively reduce the production of the immunosuppressive molecule prostaglandin E2 (PGE2 ) and hence reduce inflammatory responses in weaner pigs experimentally infected with an enterotoxigenic strain ofE. coli . Methods The experiment was conducted in a research facility with 192 individually-housed male weaner pigs (Landrace × Large White) weighing 6.6 ± 0.04 kg (mean ± SEM). The pigs were experimentally infected with an enterotoxigenic strain ofE. coli and were allocated to a 2 × 3 factorial design with the respective factors being without and with 125 ppm ASA and three levels of Vit E supplementation (50, 100 or 200 IU/kg diet, dl -α-tocopheryl acetate). Results Acetylsalicylic acid supplementation improved average daily gain (P <  0.05) and tended to improve feed:gain ratio (P <  0.10) during the first 14 d after weaning. Acetylsalicylic acid supplementation also improved (P  < 0.001) amino acid utilization efficiency (as assessed by plasma urea level) and tended to decrease (P  < 0.10) PGE2 production in the liver without affecting small intestinal histology and tight junction protein mRNA expression in the jejunal epithelium. Vitamin E supplementation greater than 100 IU/kg diet sustained both the plasma Vit E concentration (P  < 0.001) and plasma haptoglobin content (P  < 0.001) after weaning. However, there was no additive effects of the combined supplementation of ASA and Vit E on performance, intestinal barrier function and inflammatory responses of weaned pigs. Conclusions Although ASA and vitamin E improved amino acid utilization efficiency and reduced acute inflammatory responses, ASA and vitamin E did not additively reduce production of PGE2 and inflammatory responses in weaner pigs experimentally infected with an enterotoxigenic strain ofE. coli .